Structural Modification of Curcumin Analogues for Enhanced Antibacterial and Antioxidant Activities: Synthesis, Characterization, and In Silico Studies - Aishwarya Patel; Dr. Kamalesh Kumar Patel (International Journal of Scientific Research in Chemistry, 2025)
Curcumin, a polyphenolic compound derived from Curcuma longa, is well-documented for its diverse pharmacological properties, including antimicrobial and antioxidant effects. However, its therapeutic potential is hindered by limitations such as poor solubility, low bioavailability, and rapid metabolic degradation. To address these challenges, this study focused on the rational design and synthesis of six novel curcumin analogues (CA1–CA6) with tailored structural modifications aimed at enhancing biological activity. The analogues were synthesized via base-catalyzed Claisen–Schmidt condensation using substituted aromatic aldehydes, introducing various electron-withdrawing and electron-donating groups. Structural integrity and purity were confirmed using FTIR, UV-Vis, ¹H NMR, ¹³C NMR, and MS analyses, with yields ranging from 68–87% and purity above 93%. Antibacterial activity was evaluated using the disk diffusion and minimum inhibitory concentration (MIC) assays against Staphylococcus aureus and Escherichia coli. CA3 and CA5, bearing nitro and chloro groups respectively, exhibited superior antibacterial efficacy (MIC: 12.5–25 µg/mL), indicating enhanced membrane permeability and target affinity. Antioxidant potential, assessed by the DPPH radical scavenging assay, showed that CA2 and CA4 (with hydroxyl and methoxy substitutions) achieved the lowest IC₅₀ values (18.2 and 21.5 µg/mL), consistent with their radical stabilization capacity. In silico molecular docking revealed strong binding affinities of CA3 and CA5 with bacterial DNA gyrase, while CA2 showed significant interaction with human peroxiredoxin. ADMET profiling predicted favorable pharmacokinetics, with all analogues adhering to Lipinski’s Rule of Five and exhibiting high gastrointestinal absorption and low toxicity. These results highlight the importance of structure-based modifications for improving curcumin’s pharmacological profile and support further in vivo and mechanistic investigations.